The mean willingness-to-pay for smoking cessation treatment in Malaysia - Chuah, Seong Jin; Mohamed Nor, Ashidah; Samdin, Zaiton; Zainal Abidin, Emilia (Inderscience, 2023)
This research aims to estimate the mean willingness-to-pay (WTP) for smoking cessation treatment among smokers in Malaysia. We analysed individual smoker's WTP based on questionnaires distributed to current smokers above 18 years of age. The mean WTP was measured using the contingent valuation method incorporating double-bounded questions and logistic regression analysis. The mean WTP (weekly) for the three proposed therapies, namely: nicotine patches, bupropion and varenicline were RM41.21, RM28.78 and RM35.74, respectively, and these values were 67.03%, 28.05%, and 45.01% lower than the current market prices for the treatments, respectively. Therefore, this study indicates that a subsidy for smoking cessation treatments is necessary and that the awareness of the available smoking cessation treatments could be raised, to increase the quit rate from smoking.